2003
DOI: 10.2307/3186134
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Party Systems between Elections

Abstract: T he existing political science account of party competition pays little attention to the evolution of legislatures between elections, despite the fact that, in all real legislatures, there is a great deal of politics between elections. In particular, legislators may defect from one party and join another, parties may split and fuse, and the party system may thereby evolve into one quite different from that produced by the election result. This carries obvious analytical implications for modeling party competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 17 publications
1
56
0
2
Order By: Relevance
“…Laver & Shepsle 1996: 110–111). Furthermore, to be a structurally stable core party in two dimensions, a party must not only be centrally located but also be the largest party (Schofield 1993: 5–13; Laver & Benoit 2003: 221; Laver & Shepsle 2000: 121–122) 7 . Furthermore, for national government formation, Laver & Shepsle (1996, 2000) and Skjæveland (2003, 2004) have suggested that the median party must be of a certain size to be able to cope with the practical tasks of government – to have ‘office capacity’ (cf.…”
Section: Coalition Formation Theorymentioning
confidence: 99%
“…Laver & Shepsle 1996: 110–111). Furthermore, to be a structurally stable core party in two dimensions, a party must not only be centrally located but also be the largest party (Schofield 1993: 5–13; Laver & Benoit 2003: 221; Laver & Shepsle 2000: 121–122) 7 . Furthermore, for national government formation, Laver & Shepsle (1996, 2000) and Skjæveland (2003, 2004) have suggested that the median party must be of a certain size to be able to cope with the practical tasks of government – to have ‘office capacity’ (cf.…”
Section: Coalition Formation Theorymentioning
confidence: 99%
“…We know much less about the question of how MPs in nascent parliaments sort into parties, that is, which party an individual MP chooses. The question of party choice has only been studied with regard to party switching in modern parliaments (Desposato ; Desposato and Scheiner ; Heller and Mershon ; Laver and Benoit ; Mershon and Shvetsova ; Thames ). According to these studies, legislators switch to parties that offer better career opportunities (e.g., to government rather than opposition parties) (Desposato ; Heller and Mershon ) and parties with better access to offices within the legislature (McElroy ) and better electoral prospects (Desposato ; Desposato and Scheiner ; Laver and Benoit ).…”
Section: How Do Mps Decide To Join a Party And Which Party Do They Chmentioning
confidence: 99%
“…Second, the decision to join a party may be driven by electoral motivations rather than policy seeking. Electoral motivations are fundamental for contemporary party switchers (Desposato ; Desposato and Scheiner ; Laver and Benoit ). This explanation presupposes established links between parties and voters, which is highly questionable for 19th‐century parliaments, where MPs won elections based on their personal standing as local notables without any role for extraparliamentary parties (on Austria: Berchtold ; on France: Duverger ; on the FA: Kramer , 74; Langewiesche , 331–32; on Italy: Scarrow ).…”
Section: A Policy‐based Theory Of Partisan Sortingmentioning
confidence: 99%
“…Answers to this question are not yet clear, despite the achievements of recent studies of party switching (e.g., Desposato, 2006;Heller and Mershon, 2003, 2009a, 2009b, 2009dLaver and Benoit, 2003;Mershon and Shvetsova, 2008a, 2008b, 2009Reed and Scheiner, 2003). Answers to this question are not yet clear, despite the achievements of recent studies of party switching (e.g., Desposato, 2006;Heller and Mershon, 2003, 2009a, 2009b, 2009dLaver and Benoit, 2003;Mershon and Shvetsova, 2008a, 2008b, 2009Reed and Scheiner, 2003).…”
Section: Introductionmentioning
confidence: 99%